Brill's companion to Valerius Flaccus - Heerink, Mark.; Manuwald, Gesine. (Brill's Companions to Classical Studies., 2014)
Brill's Companion to Valerius Flaccus is the first English-language survey on all key aspects of this Flavian poet and his epic Argonautica (1st century CE). A team of international specialists offers both an account of the state of the art and new insights. Topics covered include textual transmission, language, poetic techniques, main themes, characters, relationship to intertexts and reception. This will be a standard point of departure for anyone interested in Valerius Flaccus or Flavian epic more generally. Contributors are: Antony Augoustakis, Michael Barich, Neil Bernstein, Emma Buckley, Cristiano Castelletti, James Clauss, Robert Cowan, Peter Davis, Alain Deremetz, Attila Ferenczi, Marco Fucecchi, Randall Ganiban, Mark Heerink, Alison Keith, Helen Lovatt, Gesine Manuwald, Ruth Parkes, Tim Stover, Ruth Taylor-Briggs, and Andrew Zissos.